Using Method of Moments Quantile Regression to examine the influences of fishery operations and their ramifications for marine water contamination - Alsaleh, Mohd; Abdul Rahim, A. S.; Bai, Keyu; Berhane, Guush (Central Fisheries Research Institute, 2025)
This study aims to investigate the dynamic impact of the fishing industry on marine water contamination in 27 European countries by taking into account the roles of fisheries output, the use of fossil fuels, economic development, and governance between 1990 and 2022. The results, which used a novel technique called the Method of Moments Quantile Regression (MMQR) in addition to factors that are fixed effect, demonstrated that, at most quantiles, there was a significant positive correlation between fishing production and marine water contamination. At the earliest and latest quantiles, fishery production significantly exacerbates marine water contamination, with a smaller impact at the lowest and a larger impact at the highest. Additionally, the data indicate that affluent EU14 countries produce more fish than developing EU13 countries, which has a significant and negative impact on the contamination of marine water. Marine water contamination from the usage of fossil fuels has increased significantly in the EU13 developing countries as compared to the EU14 wealthy countries. Policymakers can reduce marine water contamination in EU14 and EU13 countries by using eco-friendly fishing gear, more sustainable fishing methods, and energy technologies like wave and tidal power.